Fighting female unemployment: the role of female ownership of bank accounts in complementing female inclusive education - Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
The purpose of the study is to assess if a policy of female inclusive education should be complemented with a policy of female ownership of bank accounts to fight female unemployment. The study therefore examines how female ownership of bank accounts moderates the incidence of female education on female unemployment. The focus is on 44 SubSaharan African (SSA) countries for the period 2004 to 2018 and the empirical evidence is based on interactive quantile regressions. The interactions are tailored such that female ownership of bank accounts influence the effect of female inclusive education on female unemployment. From the empirical findings, it is evident that female ownership of bank accounts does not effectively moderate female education in order to reduce female unemployment unless complementary policies are considered. The complementary policies should be in view of boosting the interaction between female education and female bank account ownership in increasing employment opportunities for the female gender and by extension, reducing female unemployment. The invalidity of the moderating effect is robust to the inclusion of more elements in the conditioning information set as well as accounting for other dimensions of endogeneity such as simultaneity and the unobserved heterogeneity. Policy implications are discussed. This study contributes to the extant literature by assessing how female ownership of bank accounts complement female inclusive education to reduce female unemployment.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Inequality; Gender; Inclusive development; Unemployment